PEMODELAN SKENARIO KEBIJAKAN PENGENTASAN KEMISKINAN DI INDONESIA DENGAN METODE PROMETHEE - Nafiah Ariyani (EKUITAS (Jurnal Ekonomi dan Keuangan), 2015)
One of the challenging issues in poverty alleviation programs is to determine the set of multi criteria which encompass aspect of inputs, process and output that yield the best alternative program. This is important due to the fact that poverty is multidimensional issue and criteria to be considered in the program are vary. This study aimed to address a challenge by employing a mutli-criteria analysis. PROMETHEE was used to assess existing various poverty alleviation patterns. In addition, a new set of policy alternative, namely a hybrid policy was introduced in order to compare with existing policies. The results show that zakat patterns performs well in terms of time to eradicate poverty, the completeness of the program, accuracy of the target, recipient satisfactory, satisfactory of the admission process, data availability, and cost management. In contrast, CSR patterns perform well in management aspect, cost of  management, data availability and satisfactory for the time of delivery program, while the pattern of government programs excel in aspects: the completeness of the program and the availability of funds. Overall, the newly introduced policy of hybrid program offers the best performance for all aspect of input, process and output in administering the poverty alleviation programs